Analisis Masalah Penjamin Mutu Pendidikan Pada lembaga Non Formal Yang Dilandaskan Pada Program Latihan Di Sekolah Sepak Bola Unibraw 82 Malang - Dwi Rudi Prasetyo; Ahmad Yusuf Sobri; Teguh Triwiyanto (Proceedings Series of Educational Studies, 2023)
Abstract: Non-formal institutions are now starting to be in demand by many people, especially to developpotential both academic and non-academic aspects. Football schools (SSB) are non-formalinstitutions that are in demand by students ranging from children to adults. This study aims toidentify the UNIBRAW 82 Malang football school training program (SSB). Thisresearch uses aqualitative discriptive approach that takes data based on interviews, observations anddocumentation. The subjects used include three people, namely: three students, a trainer, anadministrator and three parents of students. This study shows that the right training program atUNIBRAW 82 football school is very influential on team performance. Themanagement function isimplemented in football schools where data is collected in the form of planning, organizing andcontrolling. Football school coaches are responsible for drawing up training plans based on the PSSIcompetition calendar. To ensure that the coach knows the athlete's ability with initial measurementsand that the athlete will adjust the training load of the exercise program made, the coach, parentsand students work together to create the training program. The mechanism of creating a trainingprogram is the way coaches, learners and parents work together to create and select a trainingprogram that fits the game plan.Keywords: Quality Assurance, Non-Formal Institutions, Football Schools, Training ProgramsAbstrak: Lembaga non formal saat ini mulai diminati oleh banyak masyarakat, terutama untukmengembangkan potensi baik segi akademis maupun non akademis. Sekolah sepak bola (SSB)merupakan lembaga non formal yang diminati oleh peserta didik mulai dari usia anak-anak sampaidewasa. Penelitian ini bertujuan untuk mengidentifikasi program Latihan sekolah sepak bola (SSB)UNIBRAW 82 Malang. Penelitian ini menggunakan pendekatan kualitatif diskriptif yang pengambilandata berdasarkan pada wawancara, observasi dan dokumentasi. Adapun subjek yang digunakanmeliputin tiga orang yaitu: tiga peserta didik, seorang pelatih, seorang pengurus dan tiga orang tuapeserta didik. Pada penelitian ini menunjukkan bahwa program latihan yang tepat di sekolah sepakbola UNIBRAW 82 sangat berpengaruh pada prestasi tim. Tiga fungsi manajemen diterapkan disekolah sepak bola tempat data dikumpulkan berupa perencanaan, pengorganisasian, danpengendalian. Pelatih sekolah sepak bola bertanggung jawab menyusun rencana latihan berdasarkankalender kompetisi PSSI. Untuk memastikan bahwa pelatih mengetahui kemampuan atlet denganpengukuran awal dan bahwa atlet akan menyesuaikan beban latihan dari program latihan yangdibuat, maka pelatih, orang tua dan peserta didik bekerja sama untuk membuat program latihantersebut. Mekanisme pembuatan program latihan adalah cara pelatih, peserta didik dan orang tuabekerja sama untuk membuat dan memilih program latihan yang sesuai dengan rencanapertandingan.Kata kunci: Penjaminan Mutu, Lembaga Non Formal, Sekolah Sepak Bola, Program Latihan